The World Bank translation style guide (Washington, 2004)
Through this bilingual approach, the translation business unit of the World Bank, which developed the Translation Style Guide in collaboration with various partners and stakeholders, hopes to reach a wide-ranging, diversified audience, with one major objective in mind: to enhance consistency in the way this institution communicates in English and in other languages.
Keywords: Biên dịch và phiên dịch,Translating and interpreting